P450 Real life Effectiveness and safety of an induction treatment with tofacitinib in patients with Ulcerative Colitis: First results of the French TOFAST cohort. (30th January 2023) - Fumery, M; Bouhnik, Y; Faure, P; Bouzidi, A; Brault, Y; Peyrin-Biroulet, L; Laharie, D
Abstract: Background: We report the results of TOFAST, a French ongoing prospective observational multicenter study, evaluating the clinical benefit of tofacitinib for the treatment of moderate to severe UC. Methods: In this descriptive interim analysis, effectiveness and safety were assessed at the end of induction therapy (up to 4 months after tofacitinib initiation). Clinical response was defined as a decrease in partial Mayo score (PMS) (≥ 3 points and ≥ 30%) from inclusion with a concomitant decrease in rectal bleeding (RB) subscore ≥ 1 point (absolute subscore of 0 or 1). Clinical remission was defined as PMS ≤2 with no subscore >1. Change in daily PRO2 scores [RB and stool frequency (SF)] during the first 14 days and the median time to patient relief were also analyzed. Results: Among the 102 patients included, 86 had available data at the first follow-up visit, corresponding to the end of induction period. At inclusion, 53.9% of patients were male with a mean (± SD) age of 37.1 ±13.6 years, a median disease duration of 6.1 years [Q1; Q3: 2.8; 10.8]. 48% of patients had pancolitis and 24.5% an extraintestinal manifestation; mean PMS was 6 ±1.8 with median SF and RB scores of 3.0 [Q1; Q3: 2.0; 3.0] and 2.0 [1.0; 2.0], respectively. Regarding prior drug exposure, 92.2% of patients had received at least one anti-TNF agent, 62.7% vedolizumab and 34.3% ustekinumab. Tofacitinib was initiated at 10 mg b.i.d, in combination with 5-ASA and corticosteroids for 19.6% and 33.3% of patients, respectively. At the first follow-up visit (median 1.9 months after treatment initiation), tofacitinib was ongoing in 87.2%, mostly (73.3%) at 10 mg b.i.d . Corticosteroids were ongoing in 29.1% of patients. At the end of induction period, rates of clinical response and remission were 52.3% and 43%, respectively. Median changes in RB and SF scores were identical at days 7 and 14, -1 point [Q1; Q3: -1.0; 0.0] and -1 point [Q1; Q3: -2.0 - 0.0], respectively. For patients who reported improvement (68.6%), the median time to relief was 7 days [Q1-Q3: 4.0-15.0]. PRO2 scores normalisation during the first 14 days is shown in the figure. RRegarding safety, 73.5% of patients reported at least one adverse event (AE) and 12.6% reported at least one serious AE. Ten (9.8%) infections (none considered as serious) and 2 (1.9%) Herpes Zoster were reported. No major cardiovascular or venous thromboembolic event, nor malignancy or death were observed (Table). Conclusion: The interim results of TOFAST study show that at the end of induction therapy with tofacitinib, 52.3% of patients achieved clinical response and >40% achieved remission. Rapid improvement in SF and RB scores was observed within 2 weeks. AEs were consistent with the known tofacitinib safety profile.